Rendahnya Implementasi Nilai-Nilai Pancasila Bagi Generasi Z Dalam Bermedia Sosial - Cindy Maharani Aulia; Naila Kirani Putri; Shaffa Tanti Yupravita; Siti Nurmuawanah (Hakim, 2024)
This research focuses on the implementation of Pancasila values for Generation Z in social media to evaluate the role and ethics of Generation Z in social media. Seeing the rapid development of information and communication technology today, to find out and get to know generation z about the extent to which they apply the values of Pancasila in interacting on social media, research was made from several cases that have occurred related to violations on social media. This research aims to investigate the tenuous relationship between Pancasila values, Generation Z behavior, and the influence of social media in shaping Generation Z's views and attitudes towards these values. In the digital age and global connectedness, social media is the main platform where generation Z interacts and receives information. This research uses qualitative and quantitative approaches to collect data through surveys and social media content analysis. This research explores the interaction between Pancasila values and Generation Z through the medium of social media. Generation Z, who grew up in the era of information technology, has extensive access to social media that influences their perception and adoption of Pancasila values. This research uses a literature analysis method to investigate how Pancasila values are reflected and conveyed in social media used by generation Z. The results of this research can provide insights into the interaction between Pancasila values and generation Z through social media. The results of this research can provide insights into how Pancasila values are reflected and conveyed in social media used by generation Z.